The zombie zone - Roy, Ron, 1940-; Gurney, John Steven, 1962- (New York : Random House, 2005)
Reports of zombies and grave-robbers alarm the people of a Louisiana swampland village, but Ruth Rose, Josh, and Dink begin to suspect that the supernatural may not be the cause of the eerie occurrences.
"A Stepping Stone book."
2.6.
Keywords: Zombies -- Fiction; Cemeteries -- Fiction; Swamps -- Fiction; Mystery and detective stories; New Orleans (La.) -- Fiction